PENDAMPINGAN BERKELANJUTAN UNTUK PRODUKSI DAN PENETAPAN HARGA - Nurlinawati Simanjuntak; Herta Manurung; Dahlia Siallangan; Hotlan Purba; Erlianti Simanjuntak; Elsameda Chairani Pinem; Samuel P Tambunan (Smart Education, 2025)
Abstract: Community service conducted by the Faculty of Economics, Unita, with the Baion